Enhancing Problem-Solving and Creative Thinking in Middle School Students through Visual Arts - Vosiyeva Aziza To‘xtaqulovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article examines methods for enhancing problem-solving and creative thinking in 5th–7th grade students through visual arts education. It focuses on project-based learning, collaborative group activities, experiential methods, and the integration of digital technologies. The study highlights that combining traditional art techniques with innovative pedagogical strategies improves students’ creative expression, analytical skills, and cognitive development, fostering well-rounded artistic competencies.